Выделение и кристаллизация рибосомного белка TS9 - Агаларов, С.Ч.; Елисейкина, И.А. (Биополимеры и клетка, 1989)
Описан метод выделения и кристаллизации рибосомного белка TS9 из экстремально термофильной бактерии Thermus thermophilus. Кристаллы имеют ромбическую форму и максимальный размер 0,5 мм. Описано метод виділення і кристалізації рибосомного білка TS9 з екстремально термофільної бактерії Thermus thermophilus. Кристали мають ромбічну форму і максимальний розмір 0,5 мм. A method is suggested to isolate ribosomal protein TS9 from SOS subparticles of ribosomes from extremal-thermophilic bacterium Thermus thermophilus. Rhomb-shaped crystals of this protein with maximal dimensions of 0.5 mm have been obtained. A method of vapour diffusion in a «hanging» drop with 2-methyl-2.4-pentanediol (MPD) as a precipitant has been used for crystallization.